Pendidikan Kristiani Inklusif-Dialogis dalam Konteks Perguruan Tinggi - Sibarani, Apriani Magdalena (JURNAL TERUNA BHAKTI, 2022)
AbstractThis paper focuses  on Christian education in the context of higher education by proposing a dialogue-inclusive Christian education model as a manifestation of religious moderation. In this regard, the author uses Edward Foley's method of theological reflection which offers a new perspective of theological reflection in interreligious context by using the term reflective believing. Reflective believing becomes a space for interreligious experiences, cultures and traditions to connect and give meaning. Reflective believing will be linked to three important elements in Christian education developed by Jack L Seymour, namely identity, vocational and resources.The result is a dialogue-inclusive Christian education model, namely Christian education as an encounter of identity, vocational and resource; Christian education as a dialogue of experience and faith traditions; Christian education as a collective action.Keywords : christian education, religious moderation, reflective believing.